MOTIVES BEHIND CONFLICT ON DOUGLAS PRESTON’S NOVEL BLASPHEMY - VICTORIA, PINKHA GITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT Conflict is a struggle over values or claims to status, power, and scarce resource, in which the aims of the conflict groups are not only to gain the desired values, but also to neutralize, injure, or eliminate rivals. Conflict occurs triggered by some factors; it could be intrenal or external factors, these factors called motives. Motivation (motive) is the force that drives us to act or behave the way we do. The motivation process progresses from thinking to feeling to action. This research focuses on conflict dimensions based on Galtung?s Theories of Conflict, also human?s basic needs as motives of dominant characters in Blasphemy that trigger conflicts. The aim of this research is to identify four conflict dimensions that is used to describe the conflict in the novel, and analyze the motives based on Abraham Maslow?s Hierarchy of Needs. The result of this research shows that the conflict in the novel is a conflict of interest and it happens between four groups, and motives behind the conflict in Blasphemy aroused from the dominant characters? physiological needs, safety needs, love and belonging needs, esteem needs, and self-actualization needs. Keyword : Conflict, motives, needs, interest, groups